Intercultural Shock in Japanese Language Learning at Bali Tourism Polytechnic - Kusumarini, Indah; Zuraida, Lukia (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2022)
The purpose of this study was to analyze the errors of students in understanding the use of Japanese according to the native cultural context of the speakers. The fault findings were analyzed from the point of view of Japanese culture and Indonesian culture. Common student errors include (1) the inappropriate application of ojigi (bowing), (2) the application of doozo speech (please), shitsurei shimasu (excuse me), sumimasen (sorry, excuse me, thank you) (2) MD sentence structure where very different from the Indonesian sentence structure, and several other errors. By looking at these misunderstandings, the understanding of Japanese cultural literacy must be taught to students. Learners must have intercultural competence so that they can communicate according to the culture of the origin of the foreign language. Several ways have been done by lecturers to improve students' cultural literacy towards understanding the use of Japanese. These methods are (1) role-playing with situations in the workplace, (2) watching videos or pictures that show the real life of Japanese people, (3) with students watching Japanese dramas, then discussing the contents of the drama.